2017
DOI: 10.9755/ejfa.2016-10-1542
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Essential Oils of Passiflora Edulis F. Flavicarpa Agroindustrial Waste

Abstract: The study of the chemical composition of essential oils of shells and seeds of Passiflora edulis f. flavicarpa is discussed. The essential oils were obtained by microwave assisted hydrodistillation (MWHD) as extraction method using Clevenger apparatus. The compounds were separated and identified by gas chromatography mass spectrometry (GC-MS). There were no significant differences of essential oil yields between samples. 20 compounds were detected altogether. Ionol was the main compound in shells (13.15%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…[70,71] In addition, fatty acids such as palmitic, oleic, undecanoic, lauric and linoleic acid have known antifungal activity, mainly against the pathogens Alternaria solani, Aspergillus niger, A. terreus, Candida albicans, Cocumerinum lagenarium, Colletrotichum lagenarium, Emericella nidulans, Fusarium oxysporum, Moniliophtora perniciosa and Pythium ultimum. [72][73][74][75][76][77] These fatty acids could be of great interest for future investigations, as fatty acid-capped silver nanoparticles have been characterised by various techniques and used to explore their potent biofungicidal properties. [78] C-Cladodes, S -spines, R -roots, Rh -Rhizosphere, Re -root endosphere and "-" -not informed.…”
Section: Antifungal Compoundsmentioning
confidence: 99%
“…[70,71] In addition, fatty acids such as palmitic, oleic, undecanoic, lauric and linoleic acid have known antifungal activity, mainly against the pathogens Alternaria solani, Aspergillus niger, A. terreus, Candida albicans, Cocumerinum lagenarium, Colletrotichum lagenarium, Emericella nidulans, Fusarium oxysporum, Moniliophtora perniciosa and Pythium ultimum. [72][73][74][75][76][77] These fatty acids could be of great interest for future investigations, as fatty acid-capped silver nanoparticles have been characterised by various techniques and used to explore their potent biofungicidal properties. [78] C-Cladodes, S -spines, R -roots, Rh -Rhizosphere, Re -root endosphere and "-" -not informed.…”
Section: Antifungal Compoundsmentioning
confidence: 99%
“…Despite the significant differences in fiber content shown in Table 1, the level can be considered as abundant in peel and seed. Regarding the oil content, P. edulis f. edulis is recognized by different authors as an oily species [38][39][40][41], with values similar to those found in fruits of greater commercial impact such as yellow passion fruit [38,42].…”
Section: Bromatological Analysis and Mineral Contentmentioning
confidence: 99%
“…Nos últimos anos, os resíduos provenientes da indústria de suco de maracujá ganham espaço e despertam interesse econômico no Brasil e no mundo, por meio do aproveitamento desses materiais (OLIVEIRA et al, 2017;MATIAS;. Assim, a indústria de alimentos pesquisa formas de aplicação dos seus resíduos, transformando-os em benefícios agregando valor nutricional e favorecendo a abordagem de novas possibilidades de utilização de partes de um fruto que seria rejeitada, correspondendo a cerca de 90% dos resíduos (SANTOS, 2015;CHÓEZ-GUARANDA, et al, 2017;EMBRAPA, 2017).…”
Section: Resíduos Do Maracujáunclassified